2008
DOI: 10.1016/j.catcom.2007.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Selective catalytic reduction of NO by NH3 over a Ce/TiO2 catalyst

Abstract: Samples of cerium supported on titania with different Ce loadings have been prepared by an impregnation method and tested for the selective catalytic reduction of NO by NH 3 in the presence of excess oxygen. The catalysts with 5% Ce and above had high activity in the temperature range 275-400°C at a space velocity of 50,000 h À1 . All the catalysts showed an excellent selectivity to N 2 and high tolerance to SO 2 and H 2 O under our test conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
140
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 313 publications
(149 citation statements)
references
References 19 publications
7
140
1
1
Order By: Relevance
“…For instance, Xu et al 72 reported a novel Ce/TiO 2 catalyst, prepared by a conventional precipitation method, showing high deNO x efficiency and N 2 selectivity from 250 to 400 1C. Afterwards, Gao et al 73,74 investigated the influence of preparation methods (including sol-gel, impregnation and co-precipitation methods) and concluded that the catalyst prepared by the sol-gel method showed the best catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Xu et al 72 reported a novel Ce/TiO 2 catalyst, prepared by a conventional precipitation method, showing high deNO x efficiency and N 2 selectivity from 250 to 400 1C. Afterwards, Gao et al 73,74 investigated the influence of preparation methods (including sol-gel, impregnation and co-precipitation methods) and concluded that the catalyst prepared by the sol-gel method showed the best catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The highest NOx conversion of 88% was gained by Ce0.3/ARM at 300 °C and 90% by Ce0.7/ARM at 350 °C. It can be viewed that red mud-based Ce/ARM catalysts have good performance for denitration in 275-400 °C, which is comparable with Ce/TiO2 (5% Ce-doped) [29] and V2O5/TiO2 catalysts [30].…”
Section: Catalytic Activity Of Ce/armmentioning
confidence: 68%
“…In our previous study, Xu et al [30] developed a promising CeO2/TiO2 catalyst, prepared [17], and (C) Mn/TiO2 [19] catalysts. Reaction conditions: (A) 500 mg sample, 500 ppm NO, 500 ppm NH3, 3% O2, N2 as balance gas, GHSV = 28 000 h −1 ; (B) 20 mg sample (0.025 mL), 2000 ppm NO, 2000 ppm NH3, 3% O2, balance He, total flow rate 138.3 mL/min, GHSV = 332 000 h −1 ; (C) 2 mL sample, 1000 ppm NO, 1000 ppm NH3, 3% O2, 3% water, balance N2, GHSV = 40 000 h −1 .…”
Section: Ceria As the Main Active Component For Nh3-scr Catalystsmentioning
confidence: 99%